2018
DOI: 10.1007/s00256-018-2942-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced magnetic resonance imaging for differentiating osteomyelitis from acute neuropathic arthropathy in the complicated diabetic foot

Abstract: Our results showed that DCE-MRI may provide reproducible parameters that can reliably differentiate osteomyelitis from acute neuropathic arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…The D (real diffusion coefficient) is also derived from the IVIM model and enables the assessment of the degree of water molecules movement without the influence of blood flow inside vessels. 50 Some authors have demonstrated that quantitative approaches may discriminate aseptic or reactive bone edema seen in Charcot foot from osteomyelitis in diabetic foot, the latter showing lower ADC values and higher transfer constants K trans and K ep values than Charcot foot 51,52 (►Fig. 9).…”
Section: Osteomyelitismentioning
confidence: 99%
“…The D (real diffusion coefficient) is also derived from the IVIM model and enables the assessment of the degree of water molecules movement without the influence of blood flow inside vessels. 50 Some authors have demonstrated that quantitative approaches may discriminate aseptic or reactive bone edema seen in Charcot foot from osteomyelitis in diabetic foot, the latter showing lower ADC values and higher transfer constants K trans and K ep values than Charcot foot 51,52 (►Fig. 9).…”
Section: Osteomyelitismentioning
confidence: 99%
“…Increased white blood cell accumulation, inflammation, and higher marrow space permeability are characteristics associated with marrow edema in OM. Whereas, in neuropathic arthropathy, marrow edema tends to have lower cellularity and cell variety in comparison to OM [90]. Cortical erosion, 'ghost sign' (relative disappearance of bone on T1-weighted image as compared to T2-weighted image), 'penumbra sign' (high signal rim of abscess on T1-weighted image) are excellent MRI signs of OM versus cysts and well-defined margins of a neuropathic bone.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…A limited number of studies have used PET/CT or MRI to measure blood flow to bone for surgical indications, including infection, osteomyelitis, and nonunion. 8 13 However, there is limited to no access to these imaging methods in real-time in the operating room. At the present time, fluoroscopy and plain radiographs are used regularly in the operating room to visualize bones and assess fracture alignment and/or hardware placement.…”
Section: Current Paradigm and Challengesmentioning
confidence: 99%